Urinary soluble alpha chain of the interleukin-2 receptor as a biomarker of active lupus nephritis in Egyptian children with juvenile systemic lupus erythematosus - Waleed HASSAN; Eman BEHIRY; Marwa MAHGOUB (Archives of Rheumatology, 2021)
Objectives: This study aims to assess the urinary soluble alpha chain of the interleukin-2 receptor (sCD25) concentrations in patients with juvenile systemic lupus erythematosus (JSLE) and to evaluate its validity to be a possible marker of disease activity in patients with lupus nephritis (LN). Patients and methods: We assessed sCD25 concentrations in urine samples obtained from 53 JSLE patients (15 males, 38 females; median age 11 years; range, 7 to 17 years) and 30 age- and sex-matched apparently healthy controls (10 males, 20 females; median age 10 years; range, 6 to 16 years). Concentrations were normalized according to urinary creatinine excretion. JSLE patients were subjected to clinical examination and assessment of overall disease activity by Systemic Lupus Erythematous Disease Activity Index (SLEDAI), while evaluation of LN activity was preformed using Systemic Lupus International Collaborating Clinics (SLICC) renal activity score. Results: The JSLE patients had significantly higher normalized urinary sCD25 concentrations compared to the healthy controls (p=0.001). Patients with active LN had significantly higher normalized urinary sCD25 levels than active JSLE patients without LN (p=0.002) and JSLE patients with inactive disease (p<0.001). A significant positive correlation was found between normalized urinary sCD25 concentrations with different activity parameters such as proteinuria (p=0.004), SLEDAI (p<0.001), renal SLEDAI (p<0.001), and SLICC renal activity score (p<0.001). A significant negative correlation was found between urinary sCD25 and complement 3 (p<0.001). Conclusion: Urinary concentrations of sCD25 were significantly elevated in JSLE patients, particularly in those with active LN. The remarkable association between urinary sCD25 concentrations and different renal disease activity parameters implies that urinary sCD25 can be a beneficial marker to monitor active nephritis in JSLE patients.